2018
DOI: 10.18203/2394-6040.ijcmph20181240
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of the pre-school children in UHTC area of Santhiram Medical College, Nandyal, Kurnool district

Abstract: Background: Malnutrition is one of the major problems in the world which suffers middle income countries in the world, malnutrition is mainly of two types over weight and underweight, the present topic is concerned to the underweight of the children among the age group between 3 yrs to 6 yrs. The aims and objectives of the study were to assess the nutritional status of children among 3-6 yrs in UHTC area of SRMC Nandyal and to identify the influence of education, occupation, and socio economic status on the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Total 451 children were enrolled in the study and the study period shown 40.1 prevalence of underweight. The data presented shows sociodemographic characteristics up to 5 years children ( 4,6,8,10 Above three-fifth of literate mothers belong to normal children and illiterate mothers belong to nearly threefifths of underweight children observed highly significant difference among education of mothers where similar finding detected by Shukla et al, Meshram et al, Vyas et al, Ebenezer et al study. 4,6,8,10 Nearly two-third of father occupation belongs to other types of job and three-fifth of labor occupation belongs to underweight children whereas four-fifth of the housewives belong to normal children and nearly two-third to underweight children observed highly significant difference among a job of parents where similar finding reported by Vyas et al study.…”
Section: Resultssupporting
confidence: 81%
“…Total 451 children were enrolled in the study and the study period shown 40.1 prevalence of underweight. The data presented shows sociodemographic characteristics up to 5 years children ( 4,6,8,10 Above three-fifth of literate mothers belong to normal children and illiterate mothers belong to nearly threefifths of underweight children observed highly significant difference among education of mothers where similar finding detected by Shukla et al, Meshram et al, Vyas et al, Ebenezer et al study. 4,6,8,10 Nearly two-third of father occupation belongs to other types of job and three-fifth of labor occupation belongs to underweight children whereas four-fifth of the housewives belong to normal children and nearly two-third to underweight children observed highly significant difference among a job of parents where similar finding reported by Vyas et al study.…”
Section: Resultssupporting
confidence: 81%